Measurement of the branching fraction B(B-u(+)->J/psi pi(+)) and search for B-c(+)->J/psi pi(+) - Abe, F; Akimoto, H; Akopian, A; Albrow, MG; Amendolia, SR; Amidei, D; Antos, J; AnwayWiese, C; Aota, S; Apollinari, G; Asakawa, T; Ashmanskas, W; et al. (1996)
We report on a measurement of the branching fraction of the Cabibbo-suppressed decay Bu +→J/ψπ+ , where J/ψ→μ+μ-. The data were collected by the Collider Detector at Fermilab during 1992-1995 and correspond to an integrated luminosity of 110 pb-1 in p̄p collisions at √s = 1.8 TeV. A signal of 289 +10 events is observed and we determine the ratio of branching fractions B(Bu +→J/ψπ+)/B(Bu +→J/ψK+) to be [5.0-1.7 +1.9(stat) ± 0.1(syst)]%. Using the world average value for B(Bu +→J/ψK+), we calculate the branching fraction B(Bu +→J/ψπ+) to be (5.0-1.9 +2.1) × 10-5. We also search for the decay Bc +→J/ψπ+ and report a 95% confidence level limit on σ(Bc +)B(Bc +→ J/ψπ+)/σ(Bu +)B(Bu +→J/ψK+) as a function of the Bc + lifetime.